Рассказы - Солженицын Александр Исаевич (Русская классика, 2018)
Экземпляры: ф-4 (20180704) / Инвентарный номер: 52285 / Цена: 188.00 / Сис.шифр: Р2 / Авт.знак: С 60 / ГРНТИ: 17.82.32 / ББК: 84 (2 Рос=Рус)6-4